Exploring Citizenship: Volunteer Guide - John Rutledge; Joy Jordan; Dale Pracht; Stacey Ellison (EDIS)
The 4-H Citizenship Project offers the opportunity to help 4-H members relate all of their 4-H projects and experiences to the world around them. The 4-H Citizenship manuals will serve as a guide for 4-H Citizenship experiences. To be truly meaningful to the real-life needs and interests of your group, the contribution of volunteer leaders is essential. Each person, neighborhood, and community has individual needs that you can help your group identify. This 6-page Volunteer Guide is a major revision written by John Rutledge, Joy C. Jordan, and Dale Pracht and published by the UF/IFAS Extension 4-H Youth Development program. https://edis.ifas.ufl.edu/4h014